A clinical study of liposuction followed by lymphovenous anastomosis for treatment of breast cancer-related lymphedema - Chang, Kun; Xia, Song; Liang, Chen; Sun, Yuguang; Xin, Jianfeng; Shen, Wenbin (Frontiers in Surgery, 2023)
Objective: In this work, we studied the clinical effect of liposuction followed by lymphovenous Anastomosis (LVAs) for treatment of breast cancer-related lymphedema (BCRL). Methods: We studied 158 patients with unilateral upper limb BCRL underwent liposuction followed by LVAs 2-4 months later. Arm circumferences before and 7 days after the combined treatments were prospectively recorded. Circumferences of different upper extremities were measured before the procedure, 7 days after LVAs and during the follow-ups. Volumes were calculated with the frustum method. During the follow-ups, the conditions of patients’ treated arms, i.e. the frequency of erysipelas episodes and dependence on compression garments, were recorded. Results: The mean circumference difference between two upper limbs decreased significantly from M (P25, P75) 5.3 (4.1, 6.9) preoperatively to 0.5 (-0.8, 1.0) (P<0.05)7 days after treatments, while at follow-up 0.3 (-0.4,1.0). The mean volume difference decreased significantly from M (P25, P75) 838.3（662.4, 1129.0）preoperatively to 7.8 (-120.3, 151.4) (P<0.05)7 days after treatments, while at follow-up 43.7 (-59.4,161.1). The incidence of erysipelas also significantly decreased (P<0.05). 6.3% patients were already independent of compression garments during the past six months or even more. Conclusion: Liposuction followed by LVAs is an effective method for the treatment of BCRL.